Traumatic Cardiac Arrest: Scoping Review of Utilization of Resuscitative Endovascular Balloon Occlusion of the Aorta - Aoki, Makoto; Abe, Toshikazu (Frontiers in Medicine, 2022)
Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) is increasingly used in trauma resuscitation for patients with life-threatening hemorrhage below the diaphragm and may also be used for patients with traumatic cardiac arrest (TCA). Resuscitative thoracotomy with aortic cross clamping (RT-ACC) maneuver was traditionally performed for patients with TCA due to hemorrhagic shock; however, REBOA has been substituted for RT-ACC in selected TCA cases. During cardiopulmonary resuscitation (CPR) in TCA, REBOA increases cerebral and coronary perfusion, and temporary bleeding control. Both animal and clinical studies have reported the efficacy of REBOA for TCA, and a recent observational study suggested that REBOA may contribute to the return of spontaneous circulation after TCA. Although multiple questions remain unanswered, REBOA has been applied to trauma fields as a novel technology.